Dear, Sincerely - Hernandez, David, 1964- (Pitt poetry series., 2016)
David Hernandez's Dear, Sincerely is his most intimate and dynamic collection to date, bringing the reader into poems that are simultaneously personal and universal, and sometimes political. With his characteristic dreamlike imagery, inventive rhythms, and biting wit, Hernandez's voice reaches toward us with an accessible profundity. Dear, Sincerely is an imaginative book that explores the Self, the collective We, the cosmos, and the murky division that separates one from the other.